Fluoroplastics. Volume 1, - Ebnesajjad, Sina (William Andrew, 2015)
Fluoroplastics, Volume 1, compiles in one place a working knowledge of the polymer chemistry and physics of non-melt processible fluoropolymers with detailed descriptions of commercial processing methods, material properties, fabrication and handling information, technologies, and applications. Also, history, market statistics, and safety and recycling aspects are covered. Both volumes contain a large amount of specific property data which is useful for users to readily compare different materials and align material structure with end use applications. Volume 1 concentrates mostly on polytetr.